Binding to DCAF1 distinguishes TASOR and SAMHD1 degradation by HIV-2 Vpx. - Michaël M Martin (Public Library of Science (PLoS), 2021)
Human Immunodeficiency viruses type 1 and 2 (HIV-1 and HIV-2) succeed to evade host immune defenses by using their viral auxiliary proteins to antagonize host restriction factors. HIV-2/SIVsmm Vpx is known for degrading SAMHD1, a factor impeding the reverse transcription. More recently, Vpx was also shown to counteract HUSH, a complex constituted of TASOR, MPP8 and periphilin, which blocks viral expression from the integrated viral DNA. In a classical ubiquitin ligase hijacking model, Vpx bridges the DCAF1 ubiquitin ligase substrate adaptor to SAMHD1, for subsequent ubiquitination and degradation. Here, we investigated whether the same mechanism is at stake for Vpx-mediated HUSH degradation. While we confirm that Vpx bridges SAMHD1 to DCAF1, we show that TASOR can interact with DCAF1 in the absence of Vpx. Nonetheless, this association was stabilized in the presence of Vpx, suggesting the existence of a ternary complex. The N-terminal PARP-like domain of TASOR is involved in DCAF1 binding, but not in Vpx binding. We also characterized a series of HIV-2 Vpx point mutants impaired in TASOR degradation, while still degrading SAMHD1. Vpx mutants ability to degrade TASOR correlated with their capacity to enhance HIV-1 minigenome expression as expected. Strikingly, several Vpx mutants impaired for TASOR degradation, but not for SAMHD1 degradation, had a reduced binding affinity for DCAF1, but not for TASOR. In macrophages, Vpx R34A-R42A and Vpx R42A-Q47A-V48A, strongly impaired in DCAF1, but not in TASOR binding, could not degrade TASOR, while being efficient in degrading SAMHD1. Altogether, our results highlight the central role of a robust Vpx-DCAF1 association to trigger TASOR degradation. We then propose a model in which Vpx interacts with both TASOR and DCAF1 to stabilize a TASOR-DCAF1 complex. Furthermore, our work identifies Vpx mutants enabling the study of HUSH restriction independently from SAMHD1 restriction in primary myeloid cells.